2020
DOI: 10.3390/ma13225259
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Influence on Ordinary Concrete Modified with Fly Ashes from Thermally Conversed Municipal Sewage Sludge Strength Parameters

Abstract: Concrete is the most commonly used structural material, without which modern construction could not function. It is a material with a high potential to adapt to specific operating conditions. The use of this potential is made by its material modification. The aim of the performed investigations was the assessment of rational application possibilities of fly ashes from thermally conversed municipal sewage sludge as an alternative concrete admixture. A concrete mix was designed, based on the Portland cement CEM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…It is quite confusing that the density of the concrete mixes with the additive is higher than that of the reference concrete, despite the higher air content of the mixes with the additive. This result is confirmed in another publication [52] describing investigations conducted by the authors and concerning application of the fly ashes from thermal conversion of sewage sludge. However, this phenomenon requires further investigations in an aim to explain its nature and reasons.…”
Section: Properties Of the Concrete MIXsupporting
confidence: 75%
See 1 more Smart Citation
“…It is quite confusing that the density of the concrete mixes with the additive is higher than that of the reference concrete, despite the higher air content of the mixes with the additive. This result is confirmed in another publication [52] describing investigations conducted by the authors and concerning application of the fly ashes from thermal conversion of sewage sludge. However, this phenomenon requires further investigations in an aim to explain its nature and reasons.…”
Section: Properties Of the Concrete MIXsupporting
confidence: 75%
“…The fly ash from thermal conversion of sewage sludge used as a substitute for cement in quantities of up to 20% results in an increase in strength if compared to the reference concrete without the addition, see Figure 6. The investigations conducted by the authors [29,30,52,53] and concerning the impact of the fly ash from thermal conversion of sewage sludge on strength compression in different maturation periods confirms the positive effect of this type of ash [29,30,52,53]. When assessing the chemical composition of the used ash [30], it was observed that for the ash obtained from the "Czajka" sewage treatment plant in Warsaw, the values of compressive strength were lower than for the concrete with the ash from the sewage treatment plant in Cracow.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…In addition, it was observed that the reference concrete showed a lower compressive strength than the FA20% samples by a value equal to 18.8% after one year of maturation. Our own experimental research conducted on the influence of fly ash from the thermal transformation of sewage sludge on the compressive strength in different maturation periods confirms the positive influence of this type of ash [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 61%
“…X’Pert Highscore software (Panalytical, Eindhoven, Netherlands) was used for processing the diffraction data. The identification of the mineral phases was based on the PDF-2 release 2010 database formalized by JCPDS-ICDD [ 7 , 27 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation